2023
DOI: 10.3390/healthcare11091319
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Needs of Older Adults Living with Dementia: An Integrative Review

Abstract: Older adults living with dementia experience progressive decline, prompting reliance on others for spiritual care and support. Despite a growing interest in studying persons living with dementia (PLwDs), empirical evidence on the spiritual needs of PLwDs has not been synthesized. Using the Whittemore and Knafl method, this integrative review examined the literature from 2000 to 2022 on the spiritual care needs of PLwDs. We sought to identify characteristics of the spiritual needs of PLwDs and ways to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…With regard to the polarity of maintaining self and being valued , a literature review of qualitative studies by Steeman et al (2006) found that people often reported a struggle to hold onto their identity, and that being understood and valued by others was important in this regard. Likewise, a literature review of spiritual needs of older adults living with dementia by Britt et al (2023) found that preserving self was an important challenge for people. What our research adds is a more pronounced polarity between intra- and inter-personal processes that are instrumental in reaffirming identity.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the polarity of maintaining self and being valued , a literature review of qualitative studies by Steeman et al (2006) found that people often reported a struggle to hold onto their identity, and that being understood and valued by others was important in this regard. Likewise, a literature review of spiritual needs of older adults living with dementia by Britt et al (2023) found that preserving self was an important challenge for people. What our research adds is a more pronounced polarity between intra- and inter-personal processes that are instrumental in reaffirming identity.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted across a range of studies (Britt et al, 2023) has highlighted the importance and delineated the spiritual needs of older people with early stage dementia living in the community. These studies revealed that the spiritual needs of this population predominantly revolved around desires to cope with memory impairment and loss of independence.…”
Section: Researches Of Spiritual Needs and Benefits For Senioros With...mentioning
confidence: 99%
“…Other benefits of spiritual care in advanced illness include reducing depressive symptoms and anxiety and maintaining social relationships. Holistic care, through daily client engagement, honors each individual's unique values and promotes their identity and personhood, which is much needed when caring for seniors with dementia throughout the course of the disease (Britt et al, 2023).…”
Section: Researches Of Spiritual Needs and Benefits For Senioros With...mentioning
confidence: 99%
“…Studies have consistently shown that spiritual care has beneficial impacts on healthrelated quality of life, hope, and coping skills and can lower anxiety, depression, and suicide in patients [24][25][26][27][28][29], regardless of their age or medical condition. This includes patients with cancer, organ failure, and dementia, among others [30][31][32][33]. Furthermore, research indicates that a healthcare team's failure to provide adequate spiritual support is linked to dissatisfaction with care, reduced use of hospice services, increased use of aggressive treatment, and higher costs [34][35][36].…”
Section: Introductionmentioning
confidence: 99%